Records Management at the Archives and Library Service of Kebumen Regency: Its Maintenance, Utilization, and Challenges - Kuswantoro, Agung; Tri Utami, Lilin Prasetyo (Program Studi Ilmu Perpustakaan UIN Alauddin, 2025)
This study investigates the maintenance and utilization of records at the Archives and Library Service of Kebumen Regency. Employing a qualitative research design with a descriptive approach, data were collected from five informants using interviews, observation, and documentation techniques. The analysis followed the Miles and Huberman model, comprising data collection, reduction, presentation, and conclusion drawing. The findings revealed two main aspects: records utilization and records maintenance. Records utilization encompasses procedures for borrowing, terms of loan, and the process of returning records. In contrast, records maintenance involves activities such as recordkeeping, arrangement, storage, and media transfer. However, the study highlighted several challenges, including the absence of formal written regulations regarding borrowing terms—both for internal and external users—and the lack of Standard Operating Procedures (SOPs) for filing and media transfer processes. Furthermore, the institution faced limitations in equipment and infrastructure necessary for the effective transfer of record media. These gaps indicated a need for policy development, procedural standardization, and investment in appropriate technologies to ensure proper records management. Strengthening these aspects is critical not only for improving administrative efficiency but also for supporting the preservation and accessibility of institutional memory within the public sector.